2017
DOI: 10.3168/jds.2016-11794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rumen undegradable protein supplementation on productive performance and indicators of protein and energy metabolism in Holstein fresh cows

Abstract: The objective of this study was to determine the effects of feeding increased dietary crude protein (CP) on productive performance and indicators of protein and energy metabolism during 21 d postpartum. Thirty multiparous Holstein dairy cows were balanced by previous lactation milk yield, body condition score (BCS) at calving, and parity and randomly allocated to 1 of 3 dietary treatments from calving until 21 d postpartum. Dietary treatments were 16.0% CP with 5.0% rumen undegradable protein (RUP) based on dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
32
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 73 publications
12
32
2
Order By: Relevance
“…Multiple metabolic factors are involved in the synthesis of urea. Therefore, one possible assumption is that the percentage of protein in the diets was above the sheep's requirements because cows given a diet with a high protein have a higher urea concentration (Amanlou et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple metabolic factors are involved in the synthesis of urea. Therefore, one possible assumption is that the percentage of protein in the diets was above the sheep's requirements because cows given a diet with a high protein have a higher urea concentration (Amanlou et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies evaluating additional protein effects prepartum found no effect (Huyler et al, 1999;Vandehaar et al, 1999;Park et al, 2002) or even a reduction (Greenfield et al, 2000;Hartwell et al, 2000) in postpartum DMI. In contrast, others reported that feeding additional protein to cows in immediate postpartum (Amanlou et al, 2017), early (Law et al, 2009), mid (Cabrita et al, 2011;Giallongo et al, 2016), and late (Barros et al, 2017) lactation increased DMI. To our knowledge, no study has examined the interaction between pre-and postpartum CP levels.…”
mentioning
confidence: 87%
“…Serum concentrations of fatty acids (colorimetric method), and BHB (enzymatic method; based on 3-hydroxybutyrate dehydrogenase) were measured by using Randox Kits (Randox Laboratories Ltd., Crumlin, UK), using a serum spectrophotometer (UNICCO, 2100, Zistchemi Co., Tehran, Iran). All serum metabolites were analyzed according to references from Amanlou et al (2016Amanlou et al ( , 2017.…”
Section: Ingredientmentioning
confidence: 99%
See 2 more Smart Citations